2005
DOI: 10.1002/prot.20695
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for SUMO‐E2 interaction revealed by a complex model using docking approach in combination with NMR data

Abstract: The interaction between small ubiquitin-related modifier SUMO and its conjugating-enzyme Ubc9 (E2) is an essential step in SUMO conjugation cascade. However, an experimental structure of such a transient complex is still unavailable. Here, a structural model of SUMO-3-Ubc9 complex was obtained with HADDOCK, combining NMR chemical shift mapping information. Docking calculations were performed using SUMO-3 and Ubc9 structures as input. The resulting complex reveals that the complementary surface electrostatic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We have now shown the high‐resolution details of this interaction and found that SUMO interacts with the N‐terminal helix, the first β‐strand and the intervening loop of Ubc9. Recently, a model for the interaction between Ubc9 and SUMO3 was created by docking approaches in combination with NMR interaction data (Ding et al , 2005). In this model, the equivalent residues of SUMO3, compared to SUMO1 in our structure, interact with Ubc9.…”
Section: Discussionmentioning
confidence: 99%
“…We have now shown the high‐resolution details of this interaction and found that SUMO interacts with the N‐terminal helix, the first β‐strand and the intervening loop of Ubc9. Recently, a model for the interaction between Ubc9 and SUMO3 was created by docking approaches in combination with NMR interaction data (Ding et al , 2005). In this model, the equivalent residues of SUMO3, compared to SUMO1 in our structure, interact with Ubc9.…”
Section: Discussionmentioning
confidence: 99%
“…Protein–protein docking refers to the prediction of the structures of protein complexes based on the structures of their constituting components, namely, receptors and ligands. One major difficulty associated with docking is that the conformational changes upon complex formation must be considered when only the structures of the separated receptor and ligand are known 1–5. For this purpose, both implicit and explicit approaches have been proposed 6.…”
Section: Introductionmentioning
confidence: 99%
“…The first, driven by the E1-SUMO complex, which mediates the transference of SUMO from the E1 to the E2 enzyme, appears dependent on residues Gln29, Arg63, Gln92, Gln94, Thr95, Gly96, and Gly97 in SUMO1, and residues Gln25, Arg59, Gln88, Gln90, Thr91, Gly92, and Gly93 in SUMO2. The second constitutes a non-covalent interaction that appears important for SUMO chain formation, and is mediated by residues Gln29, Glu33, Arg63, Leu65, Glu67, Gly81, Glu85, Asp86, Val87, Glu89, and Tyr91 in SUMO1, and Gln25, Val29, Arg59, Arg61, Asp63, Glu77, Glu81, Asp82, Thr83, Asp85, and Phe87 in SUMO2 [62][63][64][65] . Out of all the residues indicated to mediate some type of interaction with Ubc9, Gln29 is absent in SUMO1α while Arg59, Arg61, and Asp63 are absent in SUMO2α.…”
Section: Discussionmentioning
confidence: 99%